A note on tuning the Catch Limit Algorithm for commercial baleen whaling - Aldrin, M.; Huseby , Ragnar Bang; Schweder, T. (J. Cetacean Res. Manage., 2023)
The Catch Limit Algorithm for commercial baleen whaling developed by the International Whaling Commission converges slowly to a steady depletion (proportion of carrying capacity), and consequently 300 years of management is proposed as horizon for tuning and computer simulation. Long-term depletion is rather insensitive to the parameter currently used for tuning, and an alternative control parameter is suggested for this purpose.